2010
DOI: 10.1055/s-0030-1267979
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Differentiation between Acute Appendicitis and Acute Mesenteric Lymphadenitis in Children

Abstract: It is not possible to accurately distinguish acute mesenteric lymphadenitis from acute appendicitis in children using clinical evaluation alone. Ultrasound should be performed in equivocal cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 21 publications
(34 reference statements)
5
42
0
2
Order By: Relevance
“…Therefore, the shortaxis diameter of LMLN can be applied for the evaluation of each age group, rather than the long-axis diameter or average diameter. This result is consistent with the concept of using the short-axis diameter as the diagnostic parameter in existing criteria [2,7,9,11,12].…”
Section: Size Gender 2-3 Yr 3-4 Yr 4-5 Yr 5-6 Yr 6-7 Yrsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the shortaxis diameter of LMLN can be applied for the evaluation of each age group, rather than the long-axis diameter or average diameter. This result is consistent with the concept of using the short-axis diameter as the diagnostic parameter in existing criteria [2,7,9,11,12].…”
Section: Size Gender 2-3 Yr 3-4 Yr 4-5 Yr 5-6 Yr 6-7 Yrsupporting
confidence: 91%
“…The current definition of MLNE is a cluster of three or more lymph nodes with short-axis diameter � 5 mm [2,9]. However, a MLN greater than 5 mm in the short-axis diameter is a common ultrasound finding in children during clinic examination and is frequently observed in asymptomatic children [7].…”
Section: Introductionmentioning
confidence: 99%
“…The current literature on the test characteristics of US for diagnosis of appendicitis is composed of mainly single‐center studies, where US has been found to have varied sensitivity (78% to 100%) and specificity (88% to 98%) . US is well known to be operator‐dependent, yet there is scant information about its performance at centers using it infrequently .…”
mentioning
confidence: 99%
“…It is now more acceptable to perform appendectomy on normal appendix with the availability of well-trained surgeons and nurses in hospitals appendectomies for normal appendix [25] . It is known by the mnemonic 'MANTRELS' and is scored as follows: right iliac fossa pain (1 point), anorexia (1 point), nausea or vomiting (1 point), right lower quadrant tenderness (2 point), rebound tenderness(1 point), elevated temperature ≥ 37.3°C (1 point), leukocytes ≥ 11 000 (2 points), and differential white blood cell count with 75% neutrophils (1 point) [26,27] . Alvarado scores have been previously shown to be relatively sensitive and specific in adults with lower right quadrant pain.…”
Section: Discussionmentioning
confidence: 99%